Perilaku Body Shaming dalam Perspektif Islam - Putri Triana Agustina; Achmad Rizal (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2023)
Body shaming is defined as a behavior of commenting and giving negative judgments related to one's body shape, physique, appearance, and size through words that can interfere with one's physical and psychological conditions. Body shaming is a phenomenon that is often found in people's lives and often this behavior is normalized, even though body shaming can have effects that cannot be underestimated for some people. This study examines body shaming behavior from an Islamic perspective by analyzing the verses of the Quran and Hadith. This research also aims to explain about body shaming behavior according to the Quran and Hadith. The method used in this research is a qualitative method through library research. The results of this study generally explain about body shaming behavior in the perspective of psychology, the views of the Quran and Hadith on body shaming behavior, and the recommendation to speak and behave well. This research also produces several findings, namely there are several verses of the Quran and Hadith that explain body shaming behavior, although they do not mention the term body shaming specifically. The Quranic verses and Hadiths that explain the prohibition of body shaming behavior include Q.S Al-Hujurat verses 11 and 12, as well as one of the Hadiths narrated by Imam At-Tirmidzi and Imam Bukhari and Imam Muslim. Keywords: Body shaming; Quran; Hadith.